Analyse de l’effet du type de tâche sur l’évolution des connaissances à la suite d’un processus d’apprentissage collaboratif - Sabine Pohl; Karine Dejean (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This longitudinal research analyses the effect of the type of task on the development of knowledge following an interaction process in a collaborative learning context. The framework for this collaborative learning is a university education. Two types of tasks are provided to the learners. They differ depending on whether or not the solution requires the comparison of points of view on the conceptual scope of what is to be learned. The data are collected through a semi-directive interview. The results show that the type of task has an effect on the development of shared knowledge.